Judaïsme et homosexualité. Entretien avec Frank Jaoui, porte-parole du Beit Haverim - Martine Gross (Genre, Sexualité et Société)
In contemporary French society, secular and often considered hostile to groupings on the basis of « community », Beit Haverim (« House of Friends » in Hebrew) represents an original association. Created at the end of the 1970’s, this group of gay Jewish Parisians came together at the beginning of the transformation of the gay movement, of which it forms an integral part. Beit Haverim takes part in the current movement of « gay plus one » associations, which is described by Elisabeth Armstrong in her analysis of gay identity construction in 1950’s San Francisco. Its development also references transformations of the French Jewish world, marked by questioning of the place of religion in Jewish identity. While Jewish places of socialization, synagogues, and cultural centers do not allow gay or lesbian affirmation, Beit Haverim allows its member to not only live their homosexuality with a dimension of collective identity, but also to find support for another dimension of identity, their Jewishness. Various rituals offered by the association give supporters the opportunity to forge a sense of integration and affirmation of these two dimensions. The « tea dance » is marked on a calendar of Jewish holidays along with unity ceremonies modeled on traditional Jewish wedding rituals. This interview with Franck Jaoui, the current spokesperson, and Martine Gross, a researcher and founding member of the association, allows us to trace the place of the ritual in the construction of gay Jewish sociabilities and identities in France.